Effects of Ripening Conditions on the ‘Lomo embuchado’ Sausage Quality - Choe, Ho Sung (Korean J Food Sci Anim Resour, 2014)
The objective of this study was to investigate the effects of two different ripening durations, with, or without adding rosemary powder, on Lomo embuchado (LEO) sausage quality. All LEOs were ripened for two different durations, 45 or 60 d, with, or without the addition of rosemary powder, as follows: 1) LEO ripened for 45 d (LER45), 2) LEO ripened for 60 d (LER60), 3) rosemary LEO ripened for 45 d (RLE45), and 4) rosemary LEO ripened for 60 d (RLE60). Significant differences were observed in both moisture and ash content, with higher moisture and less ash content in LER45 (p<0.05). No trend was shown in the crude protein content of the four different treatments, but significantly low protein content was shown only in RLE45 (p<0.05). Ripening for 45 d improved the lightness, yellowness, and water activity of LEOs (p<0.05). However, ripening duration together with rosemary powder addition had no significant effects on redness (p>0.05). The LER45 generated significantly improved chewiness, gumminess, and hardness, as compared to both LER60 and RLE60 (p<0.05). In conclusion, the results suggest that ripening for 45 d seems to enhance LEO quality, but that rosemary powder addition may not be required to develop good LEO quality.